MeDe Innovation Fifth Annual Meeting and 3D Medical Expo 2018. Issue 2 (30th April 2018) - Mannan, Sonia
This conference report summarizes highlights from the MeDe Innovation Fifth Annual Meeting, and the 3D Medical Expo.